AGILE GOVERNANCE: RESPONS PEMERINTAH KABUPATEN INDRAGIRI HILIR TERHADAP PEMBERITAAN INFRASTRUKTUR PUBLIK DI MEDIA MASSA TAHUN 2022 - Oktafandi, Oki; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
In mid-2022, the Regional Government of Indragiri Hilir Regency faced a wave of criticism in the media regarding damaged public infrastructure, specifically the bridge on Section 17 in Sungai Piring, the bridge on Section 11 in Tekulai Hilir Village, the bridge on Section 43 in Igal Village, and Terusan Mas Parit 18 Road. This study applies agile governance theory to analyze each step taken by the Indragiri Hilir Regency government. The research method employed is qualitative, with a descriptive explanation. The types of data used include primary data, obtained from research informants, and secondary data, collected from relevant documents that support the study. The research location is within the Government environment of Indragiri Hilir Regency. The study results indicate that the Indragiri Hilir Regency government responded to public complaints about damaged infrastructure in 2022 mostly in line with the indicators of agile governance theory, though improvements and evaluations are still needed, particularly for the indicator of simple design and continuous refinement. The based on quick wins indicator focuses on the Regency government’s swift response, from the onset of media reports to the completion of infrastructure repairs. The business-driven indicator emphasizes the government's financial management ability in repairing the four pieces of public infrastructure. Good enough governance focuses on the local government’s communication strategy through social media to maintain public trust despite reports of damaged infrastructure. The human-focused indicator examines public participation, analyzing the power of community concern through media advocacy. Simple design and continuous refinement centers on the approach to reporting damaged infrastructure and implementing a simplified digital reporting design. The systematic and adaptive approach focuses on the systematic and adaptive steps taken by the government to prevent public infrastructure damage, particularly bridges and roads. Keywords: Agile Governance, Response, Public Infrastructure.